2015
DOI: 10.1016/j.jpba.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

A validated liquid chromatography tandem mass spectrometry method for quantification of erlotinib, OSI-420 and didesmethyl erlotinib and semi-quantification of erlotinib metabolites in human plasma

Abstract: A validated liquid chromatography tandem mass spectrometry method for quantification of erlotinib, OSI-420 and didesmethyl erlotinib and semi-quantification of erlotinib metabolites in human plasma, 2015, Journal of Pharmaceutical and Biomedical Analysis, (107), [186][187][188][189][190][191][192][193][194][195] The substances were extracted using protein precipitation, separated on a BEH XBridge C18 column (100 x 2.1 mm, 1.7 µm) by gradient elution at 0.7 mL/min of acetonitrile and 5 mM ammonium acetate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…1 (C)), OSI-420 and erlotinib with retention times of 1.1 and 2.2 min, respectively, could be separated from other peaks. Previous studies demonstrated that OSI-413 (desmethyl erlotinib), an isomeric metabolite of OSI-420, was observed between the retention times of OSI-420 and erlotinib in reversed-phase HPLC [16,17]. In those studies, the peak area of OSI-413 was larger than that of OSI-420.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 95%
See 1 more Smart Citation
“…1 (C)), OSI-420 and erlotinib with retention times of 1.1 and 2.2 min, respectively, could be separated from other peaks. Previous studies demonstrated that OSI-413 (desmethyl erlotinib), an isomeric metabolite of OSI-420, was observed between the retention times of OSI-420 and erlotinib in reversed-phase HPLC [16,17]. In those studies, the peak area of OSI-413 was larger than that of OSI-420.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 95%
“…Several analytical methods have been developed using liquid chromatography-tandem mass spectrometry (LC/MS/MS) [11][12][13][14][15][16][17] or high-performance liquid chromatography with ultraviolet detection (HPLC-UV) [3,18,19] to determine the concentrations of erlotinib and/or OSI-420 in human biological samples. LC/MS/MS methods are highly selective and sensitive, but due to their cost and complexity, they are not available in most hospital laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Although more solvents can be used, these are not always compatible or less suitable for direct injection into the chromatographic system with most used separation techniques. One method to increase the efficiency of PP is the use of ice-cold PP reagent [26,84], or even cooling to -80ºC on an ethanol/dry ice bath [26]. Cold-induced denaturation of proteins is a phenomenon that is caused by a temperature-dependent interaction of nonpolar groups within the protein with water.…”
Section: Protein Precipitationmentioning
confidence: 99%
“…For a number of known active metabolites, a quantitative assay has been reported, except for O-debenzyl-lapatinib, N-desmethyl-osimertinib, hydroxy-and N-desmethylpazopanib, N-deacetyl-trametinib, and hydroxy-ruxolitinib metabolite M5 (see Table 4). One of the main reasons for the absence of metabolite quantification is the lack of commercial standards at the time of development of the assay [84]. Alternatively, papers from Vikingsson et al [133] reported quantification of the metabolites relative to their parent compound, or a related metabolite of which an analytical standard is readily available [84,132,133].…”
Section: Metabolite Analysismentioning
confidence: 99%
See 1 more Smart Citation